Comparative study of substrate free and amniotic membrane scaffolds for cultivation of limbal epithelial sheet - Hyun Jung Lee (Nature Portfolio, 2018)
Abstract Transplantation of cultivated limbal epithelial transplantation has been proven to restore the corneal surface in limbal stem cell deficiency (LSCD). Here we comparatively investigated the optimized conditions and the efficiency of limbal epithelial sheet growth in three media conditions as well as with substrate free (transwell), human amniotic membrane (HAM) sutured onto transwell inserts (HAMTW), and HAM slide scaffold (HAMS). Outcomes evaluated were outgrowth sheet size from limbal explants, expression of stem/progenitor cell markers p63α, ABCG2 and CK15, and colony formation efficiency (CFE). Additionally, limbal epithelial sheets on HAMS were transplanted into corneas of LSCD rabbit models. Limbal epithelial sheets with 5% human AB serum showed the greatest increase in ABCG2 efflux activity (JC1low), p63α expression, and CFE compared in both conditions without HAM and with HAM, respectively. The outgrowth sheet size, cell yield, and Ki67 expression were increased in limbal epithelial sheets on HAMS compared to transwell and HAMTW. ABCG2 efflux activity, p63α and CK15 expressions, and CFE were also increased in limbal epithelial sheets on HAMS as well. In corneas of transplanted rabbit LSCD models, p63α expressions were noted in the basal layers and CK12 expressions were observed in superficial layers. Cultivation of limbal epithelial sheet on HAMS with xeno-free medium enhances the growth and stemness of limbal epithelial sheets.